2016
DOI: 10.1556/0806.43.2015.054
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Drought Stress on Photosynthesis Factors in Wheat Genotypes during Anthesis

Abstract: Drought is one of most important environmental factors inhibiting photosynthesis and decreasing growth and productivity of plants. The sensitivity of crop plants such as wheat to soil drought is particularly serious during reproductive phase is extremely sensitive to plant water status. The aim of this work was to study the effects of drought stress on photosynthesis, photosynthetic pigments, soluble proteins, α-tocopherol and abscisic acid content in six wheat genotypes, two tolerant (Daric and 92 Zhong), two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 30 publications
(23 reference statements)
3
14
0
1
Order By: Relevance
“…Drought stress is caused by the reduction of soil moisture content and groundwater level after prolonged water stress/dry spells which eventually leading to the cessation of plant growth [31]. Depending on the growth stage, intensity and duration of the stress, and nature of plant stress response mechanisms; drought stress causes a decrease in RWC, chlorophyll degradation, stomatal closure, increased osmolytes, and growth inhibition in wheat [32][33][34][35] which ultimately leading to yield loss and productivity. Previous reports demonstrated that water deficit (drought stress) in wheat [36,37] has unfavorable effects on the efficiency of photosystem II (PSII), as indicated by changes in chlorophyll florescence (CF) [38] parameters such as initial fluorescence (Fo), maximum quantum yield of PSII (Fv/Fm), maximum primary yield of PSII photochemistry (Fv/Fo), as well as plant growth and dry matter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drought stress is caused by the reduction of soil moisture content and groundwater level after prolonged water stress/dry spells which eventually leading to the cessation of plant growth [31]. Depending on the growth stage, intensity and duration of the stress, and nature of plant stress response mechanisms; drought stress causes a decrease in RWC, chlorophyll degradation, stomatal closure, increased osmolytes, and growth inhibition in wheat [32][33][34][35] which ultimately leading to yield loss and productivity. Previous reports demonstrated that water deficit (drought stress) in wheat [36,37] has unfavorable effects on the efficiency of photosystem II (PSII), as indicated by changes in chlorophyll florescence (CF) [38] parameters such as initial fluorescence (Fo), maximum quantum yield of PSII (Fv/Fm), maximum primary yield of PSII photochemistry (Fv/Fo), as well as plant growth and dry matter.…”
Section: Introductionmentioning
confidence: 99%
“…Several drought stress experiments in wheat were focused on the post-anthesis and/or reproduction stage [32,45] due to its imminent importance to grain yield [46]. An accumulation of evidence suggested that drought stress screening at the early growth stage hydroponically in the growth chamber [43,47] and soil conditions in the greenhouse [48][49][50][51] enables us to better define the drought stress and manage a large set of genotypes under controlled growing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Photosynthetic activity in plants has been shown to be a trait that is highly responsive to water deficit stress (Singh et al, 2014;Serba and Yadav, 2016;Perdomo et al, 2017). In wheat, a direct correlation exists between imposed water-deficit stress and decreases in photosynthetic rate, leading to changes in intercellular CO 2 concentration, stomatal conductance, and transpiration rate (Subrahmanyam et al, 2006;Balla et al, 2014;Sharifi and Mohammadkhani, 2016;Perdomo et al, 2017;Senapati et al, 2018). Water deficit stress negatively affects maximal quantum yield of PSII photochemistry (F v /F m ) (Tian et al, 2017), and damages the oxygen-evolving complex of PSII and its reaction centers (Aro, 2004;Murata et al, 2007;Tian et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The significant increase in the amounts of carotenoids in the seed filling stage as well as its increase under drought stress indicates its role in regulating the amounts of active oxygen radicals. Sharifi and Mohammad Khani stated that long‐term drought stress reduced total chlorophyll content, which occurred more significantly in susceptible wheat cultivars than drought resistant cultivars.…”
Section: Resultsmentioning
confidence: 99%